2018
DOI: 10.1038/s41467-018-05744-x
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced mechanical response in crosslinked liquid-crystalline polymers with photoswitchable glass transition temperatures

Abstract: Energy conversion of light into mechanical work is of fundamental interest in applications. In particular, diligent molecular design on nanoscale, in order to achieve efficient photomechanical effects on macroscopic scale, has become one of the most interesting study topics. Here, by incorporating a “photomelting” azobenzene monomer crosslinked into liquid crystalline (LC) networks, we generate photoresponsive polymer films that exhibit reversible photoswitchable glass transition temperatures (Tg) at room temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 48 publications
1
112
0
5
Order By: Relevance
“…Subsequent examination of the effect of the block copolymer architecture on the adhesive property revealed that the terminal PAz blocks contribute to enhance the adhesion strength and lower the residual adhesion strength upon UV irradiation. This is because these terminal PAz blocks functioned as physical crosslinks in the solid state and also imparted polymer chain mobility when softened by UV irradiation . Consequently, the 4‐arm (AB) 4 star‐block copolymers with high molecular weight ( M w ) of 136 kg mol −1 exhibited the strongest adhesion of 3.15 and 2.67 MPa for the thermoset and photoset specimens, respectively, while maintaining a relatively low residual adhesion strength of 0.45 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent examination of the effect of the block copolymer architecture on the adhesive property revealed that the terminal PAz blocks contribute to enhance the adhesion strength and lower the residual adhesion strength upon UV irradiation. This is because these terminal PAz blocks functioned as physical crosslinks in the solid state and also imparted polymer chain mobility when softened by UV irradiation . Consequently, the 4‐arm (AB) 4 star‐block copolymers with high molecular weight ( M w ) of 136 kg mol −1 exhibited the strongest adhesion of 3.15 and 2.67 MPa for the thermoset and photoset specimens, respectively, while maintaining a relatively low residual adhesion strength of 0.45 MPa.…”
Section: Discussionmentioning
confidence: 99%
“…Generally,inorganic and crystalline materials are brittle in comparison with soft materials [33] and thus in isolation they are unlikely to fulfill au seful technological role in which predictable macroscopic responses to irradiation are required. We describe herein am acroscopic photoactuation device in which the photoactive MOF is combined with polyvinyl alcohol (PVA) to form acomposite membrane.Itis known that the orientation and distribution of photoresponsive moieties in composite membranes can play acritical role in modulating the photomechanical actuation.…”
Section: Zuschriftenmentioning
confidence: 99%
“…The intensity, wavelength, and polarization of light facilitate precise control of the reactivity, selectivity, geometry, and other properties . Diverse applications for photoinduced solid–liquid phase transition materials have been proposed, for example, photopatterning, photoactuators, transfer printing, self‐healing materials, remote shutters, energy storage materials, and phototunable adhesives …”
Section: Introductionmentioning
confidence: 99%
“…There are only a few polymers reported, which exhibit a polymer glass–liquid phase transition: azobenzene‐based poly(meth)acrylates and a cross‐linked liquid‐crystal (LC) polymer with an azobenzene‐based cross‐linker . The mechanism of the phase transition was based on glass‐transition temperatures ( T g 's) that were above room temperature for the trans ‐form and below it for the cis ‐form . As polymer structure–phase transition behavior relationships are of fundamental interest, the effect of the length of methylene spacers, connecting the polymerizable group and the side‐chain azobenzene moiety, was investigated .…”
Section: Introductionmentioning
confidence: 99%